Dampak Program Kuliah Kerja Lapangan Pengabdian Pada Masyarakat (KKL-PPM) Terhadap Peningkatan Kompetensi dan Pemberdayaan Masyarakat Di Pekon Muara Dua dan Karang Rejo Kabupaten Ulu Belu - hardianpratama, reza; Khairunnisa, Khairunnisa; Nursari, Ayu; Sejati, Hiro; Wahyudi, Heru (Jurnal Khazanah Intelektual, 2026)
The KKL-PPM Program (Field Work Study – Community Empowerment Learning) is an academic initiative designed to apply students’ knowledge through direct engagement with the community. This study aims to analyze the impact of the KKL-PPM program on improving community competence and empowerment in Pekon Muara Dua and Karang Rejo, Ulu Belu District. The study involved 385 respondents and employed Smart-PLS as the analytical tool. The results indicate that the KKL-PPM program makes a significant contribution to improving community competence in entrepreneurship, digital literacy, and sustainable agricultural practices. In addition, the program fosters community empowerment by strengthening social participation, independence, and collaborative problem-solving between students and local residents. Overall, the implementation of the KKL-PPM program has produced positive and sustainable impacts, promoting continuous learning and local development in the target villages. The findings of this study have important implications for higher education institutions, local governments, and communities. For universities, the results emphasize the importance of implementing community service programs based on empowerment and sustainable knowledge transfer. The KKL-PPM model should continue to be developed using a participatory approach, where students act not only as facilitators but also as learning partners for the community. This study provides both theoretical and practical contributions to the development of community-based education models. Theoretically, it enriches the literature on the relationship between higher education, social empowerment, and the improvement of community competence through a community-based learning approach. Keywords : KKL-PPM, Community Empowerment, Competency Improvement, Ulu Belu Community Development